Interpersonal communication patterns between owner and employees in the management of UMKM MAN MUN in Gorontalo City - Maman Musa; Zenab Muhammad; Nur Fain Asmada; Anes Yawati Ismail (CERED Indonesia Publishing, 2026)
This study aims to analyze the patterns of interpersonal communication between the owner and employees in the management of UMKM Man Mun in Gorontalo City. The research employs a qualitative approach with a descriptive research type. Data were collected through semi-structured interviews, direct observation, and documentation. The informants in this study consisted of three individuals: one owner and two employees. The data analysis technique refers to the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results reveal that interpersonal communication within the organization is informal, direct, and familial. The owner provides instructions verbally and via short messages, while also showing concern for the personal situations of employees.